Paleomagnetic studies of rapakivi complexes in the Fennoscandian Shield : Implications for the origin of Proterozoic massif-type anorthosite magmatism - Salminen, Johanna; Elming, Sten-Ake; Mertanen, Satu; Wang, Chong; Almqvist, Bjarne; Moakhar, Mohsen Oveisy (Precambrian Research, 2021)
Paleomagnetic studies have been performed on five rapakivi related complexes in Sweden and Finland. Poles of varying quality have been defined and the majority of the similar to 1640-1497 Ma poles are clustering on low latitudinal positions. By combining data from similar to 1500 Ma intrusions a new high-quality pole (Plat: 13 degrees N; Plon: 190 degrees E; A(95): 11 degrees, K: 14) for Baltica has been defined. Tectonic reconstructions, on the basis of the new data and previously published high-quality data, indicate that Baltica experienced stable low latitude to equatorial positions during 1640-1470 Ma, temporally coinciding with globally pronounced rapakivi-anorthosite magmatism. Our study argues against single hotspot source for similar to 1640-1620 Ma, similar to 1590-1520 Ma, and 1470-1410 Ma rapakivianorthosites, but supports a model of large-scale superswell under a stationary low-latitude position of supercontinent Nuna for the origin of rapakivi-anorthosite magmatism. However, a possibility for convergent tectonism as the origin cannot be ruled out. Peer reviewed